IMPACT OF THE CAPITAL STRUCTURE AND EARNING MANAGEMENT TO PRUDENCE: INFORMATION ASYMETRIS AS MODERATION VARIABLE - Ramdani, Safier (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The objective of this study is to analyse the influence of capital structure and profit management on prudence, as well as to analyze the asymmetric influences of information as a moderation variable on capital structures and profits management on accounting prudence. The method used is quantitative statistical analysis, using secondary data of the annual reports of companies listed on the Indonesian Stock Exchange in 2021-2022 sectors of consumer non-cyclicals and consumer cyclical. The results of this study found that capital structures have a significant positive influence on prudence, profit management has a significant negative influence upon prudence. Control variables such as profitability and corporate size have no significant negative influence on prudence. This research contributes to the literature on accounting prudence practices that information asymmetry can prove to be a moderation variable for capital structure and profit management versus prudence.